2002
DOI: 10.1172/jci200214861
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of Gas6 for glomerular injury in nephrotoxic nephritis

Abstract: Growth-arrest specific gene 6 (Gas6) is a vitamin K-dependent growth factor for mesangial and epithelial cells. To investigate whether Gas6 is essential for progressive glomerular injury, we constructed Gas6 -/-mice and examined the role of Gas6 in accelerated nephrotoxic nephritis (NTN), a model of progressive glomerulonephritis. We found less mortality and proteinuria in Gas6 -/-mice than in wild-type mice following injection of nephrotoxic serum. Glomerular cell proliferation, glomerular sclerosis, crescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Significantly, warfarin administration at subclinical doses inhibits these increases, further supporting the involvement of vitamin K (and Gas6) in the disease aetiology. In addition, Gas6 knockout mice were less susceptible to developing accelerated nephrotoxic nephritis than wild-type animals [32]. Gas6 up-regulation was also reported in conjunction with allograft rejection in a rat kidney transplant rejection model [33] as well as in dysfunctional human renal allografts [34].…”
Section: Functions Of Gas6 As Ligand For Axl Rtksmentioning
confidence: 89%
“…Significantly, warfarin administration at subclinical doses inhibits these increases, further supporting the involvement of vitamin K (and Gas6) in the disease aetiology. In addition, Gas6 knockout mice were less susceptible to developing accelerated nephrotoxic nephritis than wild-type animals [32]. Gas6 up-regulation was also reported in conjunction with allograft rejection in a rat kidney transplant rejection model [33] as well as in dysfunctional human renal allografts [34].…”
Section: Functions Of Gas6 As Ligand For Axl Rtksmentioning
confidence: 89%
“…13 In mouse model of glomerular nephritis, Yanagita and coworks, showed that, opposite to the function of Mer, ligand binding to Axl may contribute to glomerular injury and the progression of chronic nephritis. 20,26 Ekman et al found the plasma sAxl concentrations were significantly higher in patients with LN and correlated with SLEDAI, but this was not confirmed by others. 14,15,27 Given these findings, it seems likely that in humans, the Mer and Axl play an important role in the pathogenesis of LN.…”
Section: Introductionmentioning
confidence: 89%
“…Whole kidney protein was homogenized in RIPA buffer (50 mM Tris at pH 7.5, 150 mM NaCl, 1% Nonidet P-40, 0.25% SDS, 1 mM Na3VO4, 2 mM EDTA, 1 mM PMSF, and 10 µg/ml aprotinin) and subjected to immunoblotting as described previously (49). Anti-E-cadherin antibody and anti-GAPDH antibody were from BD Biosciences -Transduction Laboratories and Research Diagnostic Inc., respectively.…”
Section: Methodsmentioning
confidence: 99%